THE PERFORMANCE ANALYSIS OF FUNCTIONAL AND RECONFIGURED LAYOUT BY MINIMISING INTERCELLULAR MOVEMENT: A CASE STUDY OF INDIAN SME (Journal of Mechanical Engineering, 2014)
Group technology (GT) utilizes a philosophy that involves grouping of components having similarmanufacturing and design attributes , known as part families (PF). In a job shop (JS) products are processedin smaller batches and with the products are changed the new processing sequence increases /changesmaterial handling within JS. Hence to reduce material handling machines need to be arranged in cells so thatmost of family members can be manufactured within the cell referred as Cellular manufacturing (CM), whichis one of the application of GT . The main goal of this research work is to present a performance comparison offunctional JS of small medium enterprise (SME) with the objective to decrease intracellular movement of partsusing newly developed approach. Effectiveness of reconfigured JS due to the proposed method and thefunctional layout is compared using six well known measures.DOI: http://dx.doi.org/10.3329/jme.v43i2.17829